Understanding the changes in multi-structure, physicochemical properties, and in vitro digestibility of quinoa starch by annealing with hydrogen-infused and plasma-activated water samples - Hang Liu; Ge Tian; Shanshan Gao; Shuang Liu (Journal of Future Foods)
We studied the combination effects of annealing (ANN) and distilled, hydrogen-infused, and plasma-activated waters on the multi-structure, physicochemical properties, and in vitro digestibility of quinoa starch (QS). To the best of our knowledge, hydrogen-infused water was used to modify starch for the first time. Compared to that of native QS, ANN-modified samples had rougher surfaces and retained the A type X-ray diffraction pattern but with higher relative crystallinity. ANN treatment significantly increased amylose content, gelatinization properties, and water absorption capacity of QS, while the swelling power and viscosity decreased. The total hydrolysis rate and rapidly digestive starch content decreased in QS after ANN treatment, and resistant starch level markedly increased. Compared to ANN with distilled water, the combination of ANN with hydrogen-infused and plasma-activated waters exhibited a higher extent of influence on the properties of QS. The sample treated with plasma-activated water showed the highest extent, which was potentially attributed to the acidic environment and the presence of reactive oxygen and nitrogen species. This research provided a novel strategy to further improve the thermal stability and functionality of starch.